Nonparametric statistical methods and the pricing of derivative securities. Issue 1 (2002) - Kiesel, Rüdiger
Abstract : In this review paper we summarise several nonparametric methods recently applied to the pricing of financial options. After a short introduction to martingale-based option pricing theory, we focus on two possible fields of application for nonparametric methods: the estimation of risk-neutral probabilities and the estimation of the dynamics of the underlying instruments in order to construct an internally consistent model.